Case report of spinal epidural abscess caused by Haemophilus paraphrophilus. - Scerpella, E G (1994)
Haemophilus paraphrophilus was recovered in pure culture from purulent material collected at surgery from a patient presenting with a spinal epidural abscess and a severe neurological deficit. This is the first report of such an occurrence.